حدیث مقبول کی معمول بہ اور غیر معمول بہ سے متعلق اصطلاحات :فنی و ادبی بحث: Terminologies of Authentic Hadith for practised and un-practised actions_ Technical and Literary Evaluation - Dr. Saima Farooq; Dr. Atiq Amjad (MEI, 2023)
Allah Almighty bestowed upon the Holy Prophet SAW comprehensive and completes Sharia and made obligatory the followings of Holy Prophet SAW. Allah Almighty created such followers of the Holy Prophet SAW to act upon His SAW sayings and actions and those followers layed down the foundations of that specific art of teminologies on the basis of solid principles and accord to keep those sayings and actions with full clarity and was known as "Muhaddiseen". The use of these terminologies according to the occasion made Islamic Literature a fruitful asset. The transfer of knowledge by use of specific terminologies has become more significant in the evolution of knowledge as compared to the primitive modes. In the present article Muhaddiseen have focused with a beacon light on this art with accuracy and unbiasedness and have drawn a red line between authentic and unauthentic sayings and have divided further the authentic sayings into practised and unpractised with minute observation. In this connection, terminologies and their meanings represent reflection of each other. The basis of these terminologies is not only on estimated ideas but also on the literary and intellectual facts. These are not only according to time and age but also historical and geographical according to the need of the hour and circumstances.